Corduroy takes a bow - Davis, Viola, 1965-; Hennessy, B. G. (Barbara G.); Wheeler, Jody; Freeman, Don, 1908-1978 (New York : Viking, an imprint of Penguin Random House LLC, 2018)
When Lisa takes Corduroy to the theater for the very first time, it s so magnificent and exciting that he just can t help heading out on his own to explore. From the orchestra pit to the prop table to the dressing rooms, Corduroy sees it all. Could there be a place for Corduroy on stage, too?
04-07.
P-02.
Keywords: Corduroy (Fictitious character); Teddy bears -- Juvenile fiction; Theater -- Juvenile fiction; Corduroy (Fictitious character) -- Fiction; Teddy bears -- Fiction; Theaters -- Fiction; Picture books for children